Peningkatan Kapasitas UMKM Kabupaten Gorontalo Utara dalam Meningkatkan Penjualan Melalui Strategi Pemasaran Digital - Yusuf, Rampi; Lahinta, Agus (Univeristas Negeri Gorontalo, 2019)
The Covid-19 virus pandemic has destroyed the most important side of the economy, namely supply and demand. From the supply side, many Micro, Small and Medium Enterprises (MSMEs) have experienced a reduction in activity due to the policy of limiting social interaction which has resulted in the cessation of the production process, and from the demand side, reduced demand for goods and services has resulted in many MSMEs unable to maximize profits. One of the economic recovery strategies is to connect with the digital ecosystem, by digitizing the market so that business actors can continue to carry out their business activities even in the midst of the Covid-19 pandemic. The goal to be achieved in this activity is to increase the capacity of MSMEs and Hutakalo village people and their sales through digital marketing strategies. The methods used to achieve these goals are socialization and training. Through outreach activities, MSMEs together with the people of Hutakalo village were given general material on digital marketing strategies and how the Hutakalo village's MSMEs and communities were able to increase the value of their business sales by using digital marketing strategies. Meanwhile, training activities are carried out to improve the skills of MSMEs and Hutakalo villagers in using the Marketplace application to market their business products, which is supported by the ability to make product photos to make them look attractive to be marketed.